1979
DOI: 10.1103/physrevlett.43.605
|View full text |Cite
|
Sign up to set email alerts
|

Massive Transfer Accompanying Proton, Deuteron, and Triton Emission in Heavy-Ion Reactions

Abstract: Fast, forward-peaked protons, deuterons, and tritons observed in the reactions of 135and 165-MeV ^% ions with ^^^'^^Sm and 166-MeV ^^F ions with ^'^Nd are shown to originate in massive-transfer reactions. These reactions are also demonstrated to have merit as probes of angular momentum space in nuclei at very high spin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Such incomplete fusion processes (also known as "absorptive break-up", "massive transfer", "internal break-up", "stripping to the continuum") have been experimentally found to contribute predominantly to the inclusive spectra of the emitted partielas [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Such incomplete fusion processes (also known as "absorptive break-up", "massive transfer", "internal break-up", "stripping to the continuum") have been experimentally found to contribute predominantly to the inclusive spectra of the emitted partielas [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…We did not consider the possibility of hotspot formation and of pre-equilibrium emission for reasons already mentioned in the introduction. Moreover, particle-7 coincidence experiments [8,29,30] support the assumption that massive transfer is the major source for these fast alpha particles.…”
Section: Discussionmentioning
confidence: 88%
“…(8) The experimental energy spectra for energetic forward alpha particles exhibit an exponentially decreasing trend [16], suggesting a Gaussian distribution for…”
Section: (Hi 9 X N) Reaction Cross Sectionsmentioning
confidence: 97%
See 1 more Smart Citation
“…A classical picture for understanding the ICF reaction process was given by Siwek-Wilczynska et al [17] for a damped projectile. However, Inamura et al [18], Zolnowski et al [19] and, Yamada et al [20] found evidence of PLFs emission through particle-γ coincidence measurements where energetic particles (Z = 1 and 2) are emitted in reactions which lead to partial fusion of the projectile with the target nucleus. The determination of input angular momentum corresponding to the heavy ion induced ICF reactions involving the emission of fast charged particles was studied by Kamanin et al [21].…”
Section: Introductionmentioning
confidence: 99%